2019
DOI: 10.1111/jace.16708
|View full text |Cite
|
Sign up to set email alerts
|

Effect of La2O3 on the oxidation resistance of SiC ceramic at 1973 K: Experimental and theoretical study

Abstract: The effect of La2O3 on the oxidation resistance of SiC ceramic at 1973 K was investigated using isothermal oxidation test and first‐principles calculations. The SiC ceramic with La2O3 shows a better oxidation resistance compared with that without La2O3 due to the in situ formed La2Si2O7 in SiO2 glass layer after oxidation at 1973 K. First‐principles calculations based on density functional theory were applied to analyze the solution behaviors of La atom in the surface of SiO2 and La2Si2O7. The solution energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…It has been also shown that the presence of interstitial La breaks the bonding between Si and O atoms to form La-O and La-Si bonds, which improves the stability of glassy SiO 2 at high temperature. [48] c. Evolution of ZrO 2 + BSG layers The fraction (as percentage of total thickness) of coarse ZrO 2 + BSG layer has been found to increase at the expense of fine ZrO 2 + BSG layer with the increase in the LaB 6 content of the composites on exposure at a given temperature (1400 °C or 1500 °C). The increase in the diffusivity of the BSG caused by the viscosity reduction through the formation of higher amount of B 2 O 3 (l) in the oxide scales of the composites with higher LaB 6 content may be considered to have promoted the coarsening of ZrO 2 grains by Oswald ripening-type mechanism.…”
Section: Mechanism Of Oxidation and Protective Scale Formation In Isothermal Conditionmentioning
confidence: 97%
“…It has been also shown that the presence of interstitial La breaks the bonding between Si and O atoms to form La-O and La-Si bonds, which improves the stability of glassy SiO 2 at high temperature. [48] c. Evolution of ZrO 2 + BSG layers The fraction (as percentage of total thickness) of coarse ZrO 2 + BSG layer has been found to increase at the expense of fine ZrO 2 + BSG layer with the increase in the LaB 6 content of the composites on exposure at a given temperature (1400 °C or 1500 °C). The increase in the diffusivity of the BSG caused by the viscosity reduction through the formation of higher amount of B 2 O 3 (l) in the oxide scales of the composites with higher LaB 6 content may be considered to have promoted the coarsening of ZrO 2 grains by Oswald ripening-type mechanism.…”
Section: Mechanism Of Oxidation and Protective Scale Formation In Isothermal Conditionmentioning
confidence: 97%
“…Exploring and developing various potential photocatalysts with high efficiency are important research areas. 9,10 The photocatalysts reported thus far involve sblock elements such as sodium (Na), potassium (K), and strontium (Sr), p-block elements such as gallium (Ga), indium (In), germanium (Ge), and bismuth (Bi), d-block elements such as titanium (Ti), nickel (Ni), cobalt (Co), and zinc (Zn), and Laseries elements such as lanthanum (La), cerium (Ce), and samarium (Sm). The photocatalytic degradation of formaldehyde begins from its adsorption and activation on the photocatalyst surface.…”
Section: Introductionmentioning
confidence: 99%